A window of opportunity against diabetes: frequency of microvascular and macrovascular complications in prediabetes - Topaloğlu, Ulaş Serkan; Göl, Mehmet Fatih; Sırakaya, Ender; Tanrıverdi, Fatih (The European Research Journal, 2023)
Objectives: To determine the chronic complications of diabetes mellitus (DM) in patients with prediabetes, and to compare prediabetics with normoglycemic group participants in terms of the presence of the complications of DM. Methods: An observational study was conducted between December 2018 to April 2019. The patients aged 18-65 years were recruited from an internal medicine outpatient clinic of a tertiary care hospital. A total of 106 prediabetic patients and 54 normoglycemic subjects were included to the study. OGTT-0th, OGTT-2nd and HbA1c levels, lipid parameters, blood pressure, the homeostasis model assessment of insulin resistan (HOMA-IR), body mass index (BMI) were estimated. Nephropathy (urine protein/urine creatinine ratio, serum creatinine [sCre], Chronic Kidney Disease Epidemiology Collaboration [CKD-EPI] equation-- creatinine clearance), retinopathy by dilated fundus examination and neuropathy (10-g monofilament testing and electroneuromyography [ENMG]) were assessed. Results: Age, gender, BMI, HOMA-IR, smoking status, lipid parameters, systolic blood pressure were similar in both groups. The values of oral glucose tolerance test (OGTT)-0th, OGTT-2nd and glycated hemoglobin (HbA1c) were higher in prediabetics. Although not statistically significant, proteinuria was slightly more occurred in the prediabetics than the controls. sCre was significantly higher, and CKD-EPI equation was significantly lower in prediabetics than in controls (p = 0.012, p = 0.001, respectively). We did not detected diabetic retinopathy in any participants. Neuropathy was slightly more occured in prediabetics, but it was not significantly different (p = 0.309). There were no correlation between sCre, CKD-EPI, proteinuria and age, BMI, HOMA-IR, OGTT-0th, OGTT-2nd, and HbA1c. Conclusions: Managing the prediabetes by early diagnosis is very meaningful in terms of prevention from DM and its complications. So, prediabetes may be a window of opportunity for diabetes associated morbidity.